Evaluation of the susceptibility of a polycaprolactone based root canal filling material to microbial degradation – An in vitro study - DR. C. GANDHIMATHI; DR. LAVANYA THANGAVELU; DR. V. PRABHAKAR (International Journal of Pharma and Bio Sciences, 2018)
The aim of this study was to evaluate the susceptibility of Resilon to biodegradation by endodontically relevant bacteria like Enterococcus faecalis, Propionibacterium acnes, Actinomyces viscosus, Pseudomonas aeruginosa and fungi like Candida albicans which are commonly present in failed root canal treatment cases. Resilon pellets dissolved in chloroform to form an emulsion were subjected to disruption using ultrasonic disrupter. This sonication procedure resulted in the formation of nanodroplets. Serial dilutions of nanodroplets of Resilon were done. Equal volume of Resilon emulsion and double strength Brain Heart Infusion Agar were mixed ,sterilized and distributed into petriplates. Endonditically related bacteria and fungi were inoculated onto culture media and zone of iinhibhition was observed after 24 and 48 hours of incubation, measured using a Computer Aided Design (CAD) software and the values were given in square cm. The values were subjected to statistical analysis using one way ANOVA followed by Post hoc test and paired test.All the test microorganisms included in the study showed significant amount of zone of clearance. It can be concluded that Resilon undergoes biodegradation. Further studies should be carried out to test the biodegradability of Resilon bound to its sealer in an environment that mimics the root canal.